Karakteristik Efusi Pleura pada Penderita TB Paru di RSUP Dr. Wahidin Sudirohusodo - Lestari, Eka Wardhana; Juhamran, Reeny Purnamasari; Anggita, Dwi; Wiriansya, Edward Pandu; Hasbi, ⁠Berry Erida; Djaharuddin, Irawaty (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
in process